Fatores críticos para o resultado de projetos de desenvolvimento de software: um estudo nas organizações brasileiras - Dal Forno, Gedson Mario Borges (2017)
Automation of processes, through the use of software, has become a widely used practice in the most diverse organizational levels. In this context, the success of software development projects has been a crucial and decisive role. The importance of defining success attributes, as well as the determination and treatment of critical factors in software development projects, can be highlighted through the several studies that have already been carried out, most of which use survey research. In order to avoid compromising the results, in this type of research, the internal validity of the research instruments used must be verified, that is, to verify if they actually measure what they propose to measure. This study was developed with the objective of developing and validating an instrument for evaluating critical factors for the outcome of software development projects, as well as determining which critical factors found for this type of projects in Brazilian organizations. For this, a bibliographic research was initially carried out aiming to define the attributes of success and the critical factors found in the literature, which, after being translated, served as a basis for the development and validation of the research instrument. After the instrument was developed and validated, it was used to perform a descriptive research of the type survey, using the quantitative methodology for the survey and analysis of the results. A total of 172 IT professionals from Brazilian organizations involved in software development projects participated in this research, to which the research instrument was applied. Statistical tests for analysis of the data were performed with the help of SPSS software (Statistical Package for the Social Sciences) version 20.0. After completing all the planned research steps, an instrument was obtained that could serve as a model for future research involving critical factors in software development projects. Also, it was possible to verify that the problems (critical factors) found in the development of this type of project remain the same over time, however, they are not receiving the attention and the appropriate treatment to obtain a success result. We conclude that for these projects, there are unique critical factors (no more of success or failure) impacting their results. On the other hand, for the projects developed in Brazilian organizations, it was determined which critical factors impact on their results. We verified the use of attributes (Scope, Quality, Time and Cost) as success descriptors. The relationships between critical factors and attributes of success were determined. The perception of the respondents, considering the methodology used, of the importance of the critical factors for the results of these projects was verified. We also verified the impact of these critical factors on projects with successful and contested results. A demonstration chart was presented for each phase of the project, with the critical factors to be monitored. Finally, the final considerations, conclusions and suggestions for future work are presented.